Low Complement C1q/TNF-related Protein-13 Levels are Associated with Childhood Obesity But not Binge Eating Disorder - İbrahim Mert Erbaş; Ahu Paketçi; Serkan Turan; Ali Rıza Şişman; Korcan Demir; Ece Böber; Ayhan Abacı (Galenos Yayincilik, 2022)
INTRODUCTION: Objective: C1q/tumor necrosis factor-related proteins (CTRPs) are recently described members of the adipokine family. CTRP-13, a new member of this family, has been shown to increase insulin sensitivity and had an anorexigenic effect on food intake in experimental studies. The aim was to investigate serum CTRP-13 levels in children with obesity, and its relationship with other adipokines, metabolic parameters, or binge eating disorder (BED). METHODS: Methods: A cross-sectional study was conducted with 105 pubertal children attending a single center. Clinical (metabolic syndrome, BED) and biochemical (glucose, insulin, lipids, leptin, adiponectin, CTRP-13 levels) parameters were assessed. RESULTS: Results: Sixty children with obesity [24 males (40%); median age 14.7 (13.0-16.4) years] and 45 healthy controls [15 males (33.3%); median age 15.2 (14.1-16.5) years] were included. Serum adiponectin and CTRP-13 levels were significantly lower in children with obesity than controls (7.1 vs 20.1 μg/mL, p<0.001; 64.7 vs 103.8 ng/mL, p<0.001, respectively). CTRP-13 levels correlated negatively with body mass index (Spearman rho=-0.230, p=0.018) and positively with high-density lipoprotein-cholesterol levels (Spearman rho=0.218, p=0.026). There was no significant difference in serum CTRP-13 concentrations in terms of the presence of metabolic syndrome or BED. DISCUSSION AND CONCLUSION: Conclusion: Childhood obesity seems to be causing dysregulation in adipokine production and function, including the down-regulation of CTRP-13. The positive correlation between CTRP-13 and HDL-C levels suggested a possible effect of this adipokine on lipid metabolism. Thus CTRP-13 may be a novel biomarker for dyslipidemia in childhood obesity.